Budidaya Ikan Lele (Clarias gariepinus) dengan Teknologi Bioflok di Pokdakan Balai Mina - raudhatus; Madyasta Anggana Rarassari; Ulfah Muharrahmah; Arief Penta Jang Jaya; Putri Nanda Zahra (Altifani Journal: International Journal of Community Engagement, 2025)
Catfish is a highly sought-after fish farmed by the community. Cultivation takes approximately 4 months from maintenance to harvest. The Balai Mina Fish Farming Group (Pokdakan Balai Mina) is a catfish farming group located in Talang Kebang Village, Pangalan Balai Subdistrict, Banyuasin Regency. The group currently focuses on cultivating catfish to consumption size. The fish harvest reaches 50 kg per week, and the farming activities are carried out sustainably. High market demand requires innovation in developing fish farming activities. The aim of this service is to provide environmentally friendly fish farming solutions using biofloc technology to increase catfish production. Catfish farming with biofloc technology results in faster growth, good feed efficiency, and a shorter rearing period, namely 2.5 to 3 months for the catfish to be harvested for consumption. Catfish farming with biofloc technology can increase fish weight by adding natural food in the pond in the form of flocs, so that the catfish receive additional food. Catfish cultivation using biofloc technology can increase catfish yields from 50 kg per week to 80 kg per week. This increase in catfish yields indicates an increase in catfish production.